(untitled) (Proceedings of Voronezh State University. Series: Geology, 2018)
Discusses the results of laboratory measurements of residual magnetization direct-seam large diameter steel pipes. Installed the predominant orientation of the vector of residual magnetization of a material in the direction of the longitudinal axis of the tube. Identified a clear link residual magnetization with the technical conditions of manufacture direct-seam pipes. On the basis of the results obtained offered total source model of magnetic anomalies arising from the studied object. The results of the decision are considered direct task of direct-seam pipes for magnetometry most practically significant cases: collinear and antiparallel the direction vectors of elements in composite pipes. The measurement results can be used to assess the technical condition of the pipelines on the basis of direct-seam steel pipe according to detailed magnetic survey data